2017
DOI: 10.18203/2319-2003.ijbcp20174769
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of atorvastatin and rosuvastatin in dyslipidemia

Abstract: INTRODUCTIONWorldwide, hypercholesterolemia cause about 56% of ischemic heart disease and 18% of strokes, resulting to 4.4 million deaths annually. Hyperlipidemia and the rates of hypercholesterolemia (total cholesterol ≥201.1mg/dl) increased from 18% to 31% in adults aged 35-59. 1 Studies have shown that the risk of ischemic heart disease in individuals with hypercholesterolemia is about thrice as great as in those with normal plasma cholesterol level indicating that reduction in plasma cholesterol does red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Thapa R et al [12] compared RSV5 with ATV10 and demonstrated significant change in LDL-C, TC, and HDL-C with both at the end of 3 rd and 6 th months. Similarly, percentage change in LDL-C, TC, and HDL-C with RSV5 was -48.69%, -35.01%, and + 25.56% respectively, while that with ATV10 was -43.85%, -34.94%, and + 8.71% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thapa R et al [12] compared RSV5 with ATV10 and demonstrated significant change in LDL-C, TC, and HDL-C with both at the end of 3 rd and 6 th months. Similarly, percentage change in LDL-C, TC, and HDL-C with RSV5 was -48.69%, -35.01%, and + 25.56% respectively, while that with ATV10 was -43.85%, -34.94%, and + 8.71% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Although there is abundant data analysing the efficacy of atorvastatin and rosuvastatin at different doses, in general, there is no analytical comparison of their lipid depleting effects in ACS patients. [8][9][10][11][12] It has been demonstrated in numerous studies that many high risk patients do not attain desired LDL-C control in spite of being treated with intensive statin therapy. [13,14] Thus, the aim of the present study was to analyse the control of LDL-C and high-density lipoprotein (HDL-C) levels after 12 weeks of statin therapy at different doses, in patients who had ACS and those who underwent revascularization with or without a prior episode of ACS.…”
mentioning
confidence: 99%